The Effects and Mechanisms of Exercise on the Treatment of Depression - Xie, Yumeng; Wu, Zuotian; Sun, Limin; Zhou, Lin; Wang, Gaohua; Xiao, Ling; Wang, Huiling (Frontiers in Psychiatry, 2021)
Background: It is necessary to seek alternative therapies for depression, because side effects of medications lead to poor adherence and some patients do not achieve a clinical treatment effect. Recently the role of exercise as a low-cost and easy-to-use treatment for depression has gained attention with a number of studies showing that exercise is effective at reducing depressive symptoms and improving body functions such as cardiorespiratory system and cognitive function. Because of the heterogeneity of exercise therapy programs, there is no standardized and unified program. Few studies have summarized the specific properties of exercise programs (type, intensity, duration, and frequency) and clinical prescriptions for exercise are not mentioned in most articles. Aims: This study aimed to investigate the feasibility and efficacy of exercise therapy for patients with depression, in order to appraise the evidence and outline accepted guidelines to direct individualized treatment plans for patients with depression based on their individual situations. Methods: A systematic review of English language literature including papers published from 2010 to present in PubMed was performed. Given the feasibility of prescribing exercise therapy for patients with depression, nearly 3 years of clinical studies on the treatments of depressive symptoms with exercise were first reviewed, comparing the exercise programs utilized. Conclusions: Exercise has therapeutic effects on depression in all age groups (mostly 18–65 years old), as a single therapy, an adjuvant therapy, or a combination therapy, and the benefits of exercise therapy are comparable to traditional treatments for depression. Moderate intensity exercise is enough to reduce depressive symptoms, but higher-dose exercise is better for overall functioning. Exercise therapy has become more widely used because of its benefits to the cardiovascular system, emotional state, and systemic functions. Recommendations: Aerobic exercise/mind-body exercise (3–5 sessions per week with moderate intensity lasting for 4–16 weeks) is recommended. Individualized protocols in the form of group exercise with supervision are effective at increasing adherence to treatment.